Analysis of the Evolutionary Trend of International Politics in the Context of the Information Age - Hu, Ruochen (Transactions on Social Science, Education and Humanities Research, 2023)
International political communication in the information age is the hot spot and focus of international public opinion, and the present era is experiencing a multidimensional, omnidirectional and deep-seated change unprecedented in a century. The subversive development of the economic pattern, the more prominent feature of information weaponized politics, the mediated politics and the politics of illusion, etc. have outlined the problematic field for contemporary international politics, preset the core issues, and depicted the inescapable undertones of the times, meanwhile, the technological factors, such as artificial intelligence, have become more important, which will reshape the international rules and institutional system. The above will become the basic trend of international politics in the context of the information age. The era defines politics, politics regulates communication, and communication maps the era. Only through proactive adaptation and planning can we find a way out of the chaos and build a new way out of the change.